Xilinx FPGA design for AC-to-AC single phase matrix converter with sinusoidal pulse width modulation / Mohamad Adha Mohamad Idin - Mohamad Idin, Mohamad Adha (2003)
The project is concerned on development of xilinx FPGA design for AC- AC single-phase matrix converter (SPMC) modulated using the widely known sinusoidal pulse width modulation (SPWM). The single-phase matrix converter (SPMC) uses 2 IGBT and 2 diode as switches to form bi-directional four-quadrant switching. Using an IGBT modules assemble the basic power switch. A converter is constructed and fed from 50V(rms), 50 Hz, supplying a passive R and RL load operated at multiple frequency of 50Hz. The model of Single Phase Matrix Converter (SPMC) is designed using computer simulation models using the Power System Block Set (PSB) within MATLab/Simulink (MLS) environment, which has been developed. The SPMC as a direct frequency changer is used in this work with the output being synthesized using the well-known Sinusoidal Phase Width Modulation (SPWM). One sine waveform with one carrier waveform is used to generate Pulse Width Modulation (PWM). The simulation result will get by using Matlab/Simulink simulation and also by using PSPICE. Xilinx is use to control the switching pattern of SPWM.